2020
DOI: 10.3389/fpsyg.2020.00836
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, Alexithymia, and Emotion Regulation in Patients With Psoriasis

Abstract: Psoriasis is a chronic dermatological condition that is frequently associated with problematic patterns of emotional reactivity (the way in which patients react to stimuli), alexithymia (their ability to recognize and label the emotional reaction), and emotion regulation (the ability to enhance or reduce their own emotional reaction). A research in the peer-reviewed scientific literature was conducted in order to identify articles describing the association of psoriasis and affective problems. In particular, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 71 publications
(120 reference statements)
1
15
0
5
Order By: Relevance
“…Patients with alexithymia are characterized by difficulties in distinguishing feelings from bodily sensations which, in turn, may alter their comprehension of the medications' therapeutic Abbreviation: BMI, body mass index; BES, Binge Eating Scale; GSI-9-K, global severity index of the Symptom Checklist-K-9; TAS-20, Toronto Alexithymia Scale role, thereby, affecting adherence. Moreover, since the ability to identify emotions strengthens the adaptive capacity of coping [47], the alexithymic lack of emotional awareness may undermine effective regulation and control over one's life [19]. Thus, for individuals with alexithymia, following healthy eating rules and prescription regimens may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with alexithymia are characterized by difficulties in distinguishing feelings from bodily sensations which, in turn, may alter their comprehension of the medications' therapeutic Abbreviation: BMI, body mass index; BES, Binge Eating Scale; GSI-9-K, global severity index of the Symptom Checklist-K-9; TAS-20, Toronto Alexithymia Scale role, thereby, affecting adherence. Moreover, since the ability to identify emotions strengthens the adaptive capacity of coping [47], the alexithymic lack of emotional awareness may undermine effective regulation and control over one's life [19]. Thus, for individuals with alexithymia, following healthy eating rules and prescription regimens may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Эти пациенты демонстрируют более высокий уровень соматизации, межличностной чувствительности, тревожности и фобической тревожности по сравнению с пациентами, не страдающими алекситимией. Повышенная распространенность алекситимии у пациентов с псориазом может привести к недооценке депрессии и суицидальности [29,31,32].…”
Section: роль психических расстройств в этиопатогенезе псориазаunclassified
“…Возможной причиной высокой распространенности депрессии у пациентов с псориазом при анализе самооценки может быть чрезмерный акцент на внешности. Также пациенты с ранним началом псориаза были значительно более депрессивными и тревожными, чем пациенты с поздним началом [2,32,51].…”
Section: роль психических расстройств в этиопатогенезе псориазаunclassified
“…13 There was no significant change in the overall score which indicates that alexithymia is a fixed trait. 14 Roh et al found a correlation between alexithymia and obsessive-compulsive symptoms. Differences between these two groups in alexithymia scale were significant.…”
Section: Introductionmentioning
confidence: 99%